The peculiarities of making the intelligence training professionally-based dialogical speech of future spesialists in the service sphere (german after english) - Okopna, Yana (My University, 2010)
The article shows how to develop students` intercultural competence in professionally-based dialogical speech (German after English) by promoting their intercultural skills and cross-cultural awareness. The research provides theoretical substantivation and practical elaboration of the methodology of training future specialists in the service sphere to use paralinguistic in German oral professional communication. Business role play helps students begin thinking in second foreign language and creates an opportunity for them to develop conversation skills and professional vocabulary.
Keywords: діалогічне мовлення; ділова гра; студенти другого курсу; немовний вищий навчальний заклад; диалогическая речь; средства обучения; немецкий язык после английского; профессионально ориентированное обучение; сфера обслуживания; communicative behaviors; culture; nonverbal communication; professionally oriented speaking; technical specialties students; кафедра іноземних мов професійного спрямування